2021
DOI: 10.31234/osf.io/exhru
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Media and Well-being: A Methodological Perspective

Abstract: Due to the methodological challenges inherent in studying social media use (SMU), as well as the methodological choices that have shaped research into the effects of SMU on well- being, clear conclusions regarding relationships between SMU and well-being remain elusive. We provide a review of five methodological developments poised to provide increased understanding in this domain: (1) the use of longitudinal and experimental designs; (2) the adoption of behavioural (rather than self-report) measures of SMU; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…For example, recent debates have focused on the negative impacts of 'screen time' on children and young adults (UK Parliament, 2018). However, many studies rely on self-reported scales or ask participants to estimate how long they spend using devices or services (known as screen time estimates), which do not align with objective logs of technology use (Ellis, Davidson, Shaw, & Geyer, 2019;Parry et al, 2021;Sewall, Bear, Merranko, & Rosen, 2020;Shaw et al, 2020). While subjective (psychometric) measures suggest that technology is inherently 'bad' for society (Ellis, 2019), pre-registered designs observe near-zero associations between well-being and objective technology use or screen time estimates (e.g., Orben & Przybylski, 2019;Shaw et al, 2020).…”
Section: Measuring and Understanding The Impacts Of Technologymentioning
confidence: 99%
“…For example, recent debates have focused on the negative impacts of 'screen time' on children and young adults (UK Parliament, 2018). However, many studies rely on self-reported scales or ask participants to estimate how long they spend using devices or services (known as screen time estimates), which do not align with objective logs of technology use (Ellis, Davidson, Shaw, & Geyer, 2019;Parry et al, 2021;Sewall, Bear, Merranko, & Rosen, 2020;Shaw et al, 2020). While subjective (psychometric) measures suggest that technology is inherently 'bad' for society (Ellis, 2019), pre-registered designs observe near-zero associations between well-being and objective technology use or screen time estimates (e.g., Orben & Przybylski, 2019;Shaw et al, 2020).…”
Section: Measuring and Understanding The Impacts Of Technologymentioning
confidence: 99%
“…Given the omnipresence of SNS and their dual effects on well-being, a key research question with practical and theoretical importance is to investigate the various conditions by which SNS may either enhance or interfere with well-being ( Ramamoorthy et al, 2021 ; Valkenburg et al, 2021 ; Hall and Liu, 2022 ; Parry et al, 2022 ). It is to understand why, how, and/or for whom SNS use is associated with well-being ( Valkenburg, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is to understand why, how, and/or for whom SNS use is associated with well-being ( Valkenburg, 2022 ). As pointed out by some recent reviews, this line of argument has predominantly relied on cross-sectional designs and self-reported measures of SNS use, which can be subject to recall ( Hall and Liu, 2022 ; Parry et al, 2022 ; Valkenburg, 2022 ). Similarly, other reviews indicate that studies on SNS use tend to focus mainly on quantity (e.g., time spent, frequency of use) without much consideration of users’ content or communication partners ( Yoon et al, 2019 ; Cingel et al, 2022 ; Oliver, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the extent to which individuals are using social media intentionally or unintentionally may enrich how we describe, study, and assess social media use. As increasing work confirms that social media affects people differently (Beyens et al, 2021;Pouwels et al, 2021), it is clear that using social media can both help and harm people's lives (Orben, 2020;Meier and Reinecke, 2021;Hancock et al, 2022), and that these effects cannot be explained by differences in time spent with social media alone (Przybylski et al, 2020;Parry et al, 2021). Examining the extent to which people use social media intentionally or unintentionally may help explain when social media is most enhancing.…”
Section: Implications For Theory and Interventionsmentioning
confidence: 99%